2021
DOI: 10.3389/fphys.2021.731416
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Markers With Specific Cut-Offs Can Predict Anemia Occurrence Among Malaysian Young Adults

Abstract: Objective: Anemia bears a high global prevalence with about 1.6 billion people living with this affliction. Malaysia carries the burden of 13.8% anemia prevalence which urges for extensive research directed to its prediction and amelioration. This is the first study that aims to (a) propose simple non-invasive predictive anthropometric markers and their specific cut-off values for early prediction of anemia among the young adults in Malaysia, (b) provide anemia prevalence based on both gender and ethnicity amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Analysis by BMI categories in the present study showed that the percentage of anaemia was found to be high among underweight students (88⋅9 %) as compared to normal (45⋅8 %), overweight (27⋅3 %) and obese participants (11⋅1 %). Studies conducted by various other scientists have also documented almost similar findings ( 10 , 32 34 , 80 ) . These findings suggest that good nutritional status reduces the risk of anaemia.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Analysis by BMI categories in the present study showed that the percentage of anaemia was found to be high among underweight students (88⋅9 %) as compared to normal (45⋅8 %), overweight (27⋅3 %) and obese participants (11⋅1 %). Studies conducted by various other scientists have also documented almost similar findings ( 10 , 32 34 , 80 ) . These findings suggest that good nutritional status reduces the risk of anaemia.…”
Section: Discussionsupporting
confidence: 64%
“…For this reason, BMI has been considered as one of the parameters to determine nutritional status of the study participants and hence nutritional anaemia. The majority of studies have associated anaemia with low BMI (31)(32)(33)(34) . Although various studies have been conducted in the past on Hb content anaemia and the associated risk factors at the national (35)(36)(37)(38)(39)(40)(41) and international levels (30,34,(42)(43)(44)(45) , information of anaemia and its association with breakfast skipping, and BMI is not available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation